CT-08 Safety and tolerability of omalizumab, a humanized anti-IgE monoclonal antibody in systemic lupus erythematosus (STOP LUPUS). (August 2018) - Gupta, Sarthak; Hasni, Sarfaraz; Davis, Michael; Poncio, Elaine; Temesgen-Oyelakin, Yenealem; Joyal, Elizabeth; Fike, Alice; Manna, Zerai; Auh, Sungyoung; Shi, Yinghui; Chan, Diana; Carlucci, Philip; et al.
Abstract : Background: Previous evidence indicates a putative pathogenic role for IgE autoantibodies in systemic lupus erythematosus (SLE). We hypothesized that Omalizumab, a monoclonal antibody that binds IgE, will reduce SLE activity by decreasing circulating IgE autoantibodies, subsequently blocking basophil activation and type I IFN responses. This study assessed the safety, tolerability, biologic and clinical efficacy of Omalizumab in mild to moderate SLE. Methods: Fifteen subjects with SLE and a Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI 2K) of ≥4 and elevated IgE autoantibodies (above 2SD of mean of healthy controls) were randomized to receive Omalizumab or placebo (2:1) added to their baseline standard of care therapy (excluding monoclonal antibodies and alkylating agents) for 16 weeks. This was followed by a 16 week open label phase and 4 week washout period. SLEDAI 2K, British Isles Lupus Assessment Group index (BILAG 2004) and Physician Global Assessment (PGA) were recorded at each visit. The Systemic Lupus Erythematosus Responder Index (SRI 4) was calculated as a composite measure of improvement in disease activity at weeks 16, 32 and 36. Type I Interferon (IFN) induced gene signature was determined using a previously validated four gene interferon score (IFI27, IFI44, IFI44L, RSAD2) using quantitative PCR. Results: No local or systemic allergic reactions occurred following Omalizumab injections. Of the 52 adverse events (AEs), 49 were reported as mild while 3 met the criteria for severe AEs. SLEDAI 2K scores improved significantly in the Omalizumab group at week 16 (p=0.038), as well as during the open label phase in subjects initially receiving placebo (p=0.020). No worsening in BILAG scores or PGA were detected. A total of 26% (4/15) patients achieved SRI4 response criteria with Omalizumab. IFN gene signature improved in subjects treated with Omalizumab (p=0.11), especially in subjects with high baseline IFN scores (p=0.052). Conclusions: Omalizumab in subjects with SLE is well tolerated and associated with improvement in disease activity potentially linked, at least in part, to modulation of type-I IFN responses. Larger randomized clinical trials are required to assess the role of this drug in patients with SLE. Trial registration: Clinical Trials registration number: NCT01716312